Proceedings of International Symposium on Heat Transfer in Gas Turbine Systems 2009
DOI: 10.1615/ichmt.2009.heattransfgasturbsyst.390
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Counter – Rotating and Traditional Axial Aircraft Low-Pressure Turbines Integral and Detailed Performacnes

Abstract: Raising requirements for aircraft engine efficiency and fuel consumption level combined with strong restrictions to engine weight and geometrical dimension pose serious challenges for engineers who are working under the new generation of engine development. These tasks require brand new flow path design approaches. The usage of a counter-rotating turbine is one of the possible ways to successfully match all these requirements. Modern aerodynamic design computational and optimization methodologies allow to fulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The design point of the GTCRC configuration is also included in all of the plots as a reference for which the relevant performance values are presented in Table L o. s For the compressor, it is evident that as the speed ratio decreases (the rotational speed of the aft stages increase) the losses significantly increase, moving the locus of maximum efficiency to lower rotational speeds, as expected [33]. For the turbine, it is interesting to note that the efficiency remains high for a wide range of rotational speeds, in accordance with the observations by Moroz et al [27].…”
Section: Component Mapssupporting
confidence: 83%
See 1 more Smart Citation
“…The design point of the GTCRC configuration is also included in all of the plots as a reference for which the relevant performance values are presented in Table L o. s For the compressor, it is evident that as the speed ratio decreases (the rotational speed of the aft stages increase) the losses significantly increase, moving the locus of maximum efficiency to lower rotational speeds, as expected [33]. For the turbine, it is interesting to note that the efficiency remains high for a wide range of rotational speeds, in accordance with the observations by Moroz et al [27].…”
Section: Component Mapssupporting
confidence: 83%
“…Fang et al [26] presented higher fidelity simulation results for a supersonic contra-rotating turbine and compared its performance to a conventional turbine stage, calculating a stagnant efficiency advantage of the contra-rotating configuration equal to 3%. Moroz et al [27] analyzed two low pressure (LP) contrarotating designs and reported that the same performance compared to a conventional turbine can be obtained with a 30% shorter and a 40% lighter component while, at the same time, off-design behavior indicated that the contra-rotating turbine efficiency is higher in a wide range of rotational speeds. Conceming the cooling air needs, apart from the reduction expected due to nozzle elimination, the results by Moroz et al indicate that contra-rotating configurations result in a lower gas heat transfer coefficient for the aft rotor; thus, there is an additional positive effect that may result in a further reduction in the cooling air flow.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2007) numerically studied the three dimensional flow in a vaneless counter rotating turbine for various tip clearances. The comparison of conventional and counter rotating turbines with respect to essential and thorough performances for different stages was presented by Moroz et al (2009). Steps of aerodynamic design of CRT, optimization and off-design performance estimation were described.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the counter rotating mechanism has been applied to the energy conversion devices used in wind power and gas turbine generation to improve the system efficiency. These applications also have a low gear ratio of 1 to 2 [4,5]. However, counter rotating devices driven by mechanical gear structure have some drawbacks including acoustic noise, mechanical losses and high maintenance cost as well as complex structure.…”
Section: Introductionmentioning
confidence: 99%